Miniatletismo Como Medio Para Mejorar La Resistencia Aerobica En Niños De 10 A 11 Años Del Grado Quinto De La Institución Educativa Teresita Montes De La Ciudad De Armenia (2015)
The mini- athletics is a new sport in Colombia, and is given to know how close form of athletics tailored to children, in this research, which seeks to identify changes that cause the mini-athletics in aerobic endurance capacity children of School Teresita Montes of the City of Armenia, Quindio, Colombia, which presents a descriptive transversal. Results: An average increase of almost aerobic capacity of children who participated in this research process, leading us to conclude that the mini-athletics helps to improve aerobic capacity of children present.